(untitled) (مجلة إحالات, 2026)
The phenomenon of resistance has presented itself as one of the most popular topics in ancient and modern creative texts, due to the close relationship between creativity and the cultural, political and social contexts emerging under it and influencing it in one way or another, not to mention the interest in art as an effective means of expressing reality and resisting its negative phenomena, internal and external, psychological, social, and political, including on the public side: resistance to colonialism, resistance to authority, resistance to injustice, resistance to existence, resistance to others. Judging from this proposition. Through this intervention, we aim to discuss one of the elements of the resistance, It is the resistance of the Algerian emigrant intellectual to the transformations of his cultural presence on the one hand, and his resistance to the representations of the Western Other that he has been formulating from the cultural margins within his cultural structure on the other hand. Let us memorize in some detail the most important cultural and psychological methods adopted in this, to apply this hypothesis, we chose the novel "How to Breastfeed with Lupus Without Biting You" by the Algerian novelist, Amara Lakhous. This is due to its representative quality, and its awareness of the circumstances of migration in its most important aspects and challenges.